Neutrophils: Many Ways to Die - Pérez-Figueroa, Erandi; Álvarez-Carrasco, Pablo; Ortega, Enrique; Maldonado-Bernal, Carmen (Frontiers in Immunology, 2021)
Neutrophils or polymorphonuclear leukocytes (PMN) are key participants in the innate immune response by its ability to execute different effector functions. These cells express a vast array of membrane receptors that allow them to recognize and eliminate infectious agents effectively, and appropriately respond to microenvironmental stimuli that regulate neutrophil´s functions such as activation, migration, generation of reactive oxygen species, formation of neutrophil extracellular traps, and mediator secretion, among others. Currently, it has been realized that activated neutrophils can accomplish their effector functions and simultaneously activate mechanisms of cell death in response to different intracellular or extracellular factors. Although several studies have revealed similarities between the mechanisms of cell death of neutrophils and other cell types, neutrophils have distinctive properties, such as a high production of reactive oxygen species (ROS) and nitrogen species (RNS), that are important for their effector function in infections and pathologies such as cancer, autoimmune diseases, and immunodeficiencies, and that also influence their mechanisms of cell death. The present work offers a synthesis of the conditions and molecules implicated in the regulation and activation of the processes of death of neutrophils: apoptosis, autophagy, pyroptosis, necroptosis, NETosis, and necrosis. This information allows for the understanding of the duality encountered by PMNs upon activation. On the one hand, effector functions are carried out to eliminate invading pathogens, but in several instances, these functions involve activation of signaling cascades that culminate in the death of the neutrophil. This process guarantees the correct elimination of pathogenic agents, damaged or senescent cells, and the timely resolution of the inflammation that is essential for the maintenance of homeostasis in the organism. In addition, they alert the organism when the immunological system is being deregulated, promoting the activation of other cells of the immune system, such as B and T lymphocytes, which produce cytokines that potentiate the microbicide functions.